Challenges of modernity and migration policy of the state: global trends and Kazakhstan’s reality - Mussina, S.T.; Khusainova, Zh.S.; Vechkinzova, Y.A.; Assanova, M.K.; Abdeshov, D.D. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: To consider the current issues of regulation of migration processes in the world – in general and in particular – in the conditions of Kazakhstan. Methods: System analysis, comparative evaluation, methods of empirical research of cases from media materials. Results: The impact of quarantine measures to prevent the spread of the coronavirus pandemic on migration processes in the countries of the world and Kazakhstan’s practice is analyzed. The problems with unregulated migration in Kazakhstan are considered, taking into account the tightening of conditions for leaving the country and entering the country due to quarantine and the state policy towards leveling the risks of deterioration of the situation of immigrants in the country. Migration policy measures aimed at stimulating ethnic repatriation to Kazakhstan and supporting the Kandas for their successful and relatively rapid adaptation to a new place, measures to regulate internal and external migration in the educational and labor spheres are presented. The main tasks of Kazakhstan’s migration policy at the present stage are defined. Considering the identified challenges and risks, emphasis is placed on the implementation of a comprehensive coordinated migration policy with the inclusion of measures for other types of policies. Conclusions: Migration regulatory authorities in Kazakhstan are currently facing the need to solve many problems, which, on the one hand, are caused by the impact of global factors (the coronavirus pandemic and political events in the world), macro-regional factors (the policy of neighboring countries on migration regulation), and the effect of internal factors (uneven development of the country’s regions, migration sentiment in Kazakh society, the situation on local labor markets). To build an effective response, coordinated actions are needed by all parties to the migration regulation process – central government agencies, local executive bodies, international organizations, non-governmental organizations, various professional associations, intermediary structures (law firms, private employment agencies, recruiting agencies, educational centers, travel agents). The article presents examples of response measures and measures that help migrants cope with the negative consequences of quarantine restrictions during the coronavirus pandemic, get support for adaptation and integration in the host society, protect the rights and ensure safety for all members of the migrant family, get help to return to their homeland.
Қазіргі заманның сын-қатерлері жəне мемлекеттің көші-қон саясаты: жаһандық үрдістер мен қазақстандық шынайылық
Вызовы современности и миграционная политика государства: глобальные тенденции и казахстанская реальность
Keywords: external migration; unregulated migration; migration policy; adaptation and integration of migrants; migration policy